Manipulating Indigenous Vegetable Tanned Leather for Use in Macramé Art - Ackah-Arthur, Judith (2017)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi In Partial Fulfillment of the Requirements for the Award of the degree Master of Philosophy in Integrated Art (Leather Technology),